2014
DOI: 10.1002/iub.1289
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin‐binding protein 2a of methicillin‐resistant Staphylococcus aureus

Abstract: Summary High-level resistance to β-lactam antibiotics in methicillin-resistant Staphylococcus aureus (MRSA) is due to expression of penicillin-binding protein 2a (PBP2a), a transpeptidase that catalyzes cell-wall crosslinking in the face of the challenge by β-lactam antibiotics. The activity of this protein is regulated by allostery at a site 60 Å distant from the active site, where crosslinking of cell wall takes place. This review discusses the state of knowledge on this important enzyme of cell-wall biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
189
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(194 citation statements)
references
References 63 publications
3
189
0
2
Order By: Relevance
“…Expression by the bacteria of the mutant enzyme transpeptidase (mutant penicillin-binding protein -PBP2 enzyme) that has a reaction center practically inaccessible to the β-lactam antibiotics but, on the other hand, perfectly capable of catalyzing the crosslinking reaction in the course of peptidoglycan synthesis, serves as another way of bacterial resistance to β-lactam antibiotics [41]. It was discovered that in order to catalyze the crosslinking of peptidoglycan the active center of the enzyme should undergo conformational change.…”
Section: Fig 3 Penicillin G (A) and Cefaclor (B)mentioning
confidence: 99%
See 2 more Smart Citations
“…Expression by the bacteria of the mutant enzyme transpeptidase (mutant penicillin-binding protein -PBP2 enzyme) that has a reaction center practically inaccessible to the β-lactam antibiotics but, on the other hand, perfectly capable of catalyzing the crosslinking reaction in the course of peptidoglycan synthesis, serves as another way of bacterial resistance to β-lactam antibiotics [41]. It was discovered that in order to catalyze the crosslinking of peptidoglycan the active center of the enzyme should undergo conformational change.…”
Section: Fig 3 Penicillin G (A) and Cefaclor (B)mentioning
confidence: 99%
“…It was discovered that in order to catalyze the crosslinking of peptidoglycan the active center of the enzyme should undergo conformational change. This conformational change is probably triggered by the interaction of the corresponding peptidoglycan fragments with the allosteric site of this enzyme [41]. Then, it was shown that some β-lactams like ceftaroline are able to interact with the allosteric site of the enzyme leading to the conformational change -opening of its active site -that enables the second molecule of ceftaroline to react with the enzyme active site, thereby finishing the enzyme inactivation [41,42].…”
Section: Fig 3 Penicillin G (A) and Cefaclor (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…This physico-chemical alteration decreases the affinity of the drug for the site and causes loss of antimicrobial activity. As an example of this, mechanism of action is seen in the literature methicillin resistant Staphylococcus aureus, and penicillin resistant Streptococcus pneumoniae [27,28]. the expulsion of the antibiotics by cell, contributing to an inadequate concentration of the drug and consequently, ineffective action.…”
Section: General Mechanisms Of Bacterial Resistancementioning
confidence: 99%
“…β-lactam antibiotics bind to penicillin binding proteins [20] however, the Methicillin Resistant S. aureus (MRSA) strain has the SCCmec (Staphylococcal Cassette Chromosome) and the mecA gene that encodes the mutation of the penicillin binding protein, avoiding binding to β-lactams antibiotics [29]. Therefore, MRSA is resistant to all penicillins, cephalosporins and carbapenems [30]. Another example is the fluoroquinolones resistance, which occurs through mutations on topoisomerases that are essential for DNA replication, and the methylation of the ribosome [31].…”
Section: Mechanisms Of Resistance: Old Aspects Of a Difficult Dealingmentioning
confidence: 99%